2023
DOI: 10.1038/s41559-022-01925-6
|View full text |Cite
|
Sign up to set email alerts
|

De novo genes with an lncRNA origin encode unique human brain developmental functionality

Abstract: Human de novo genes can originate from neutral long non-coding RNA (lncRNA) loci and are evolutionarily significant in general, yet how and why this all-or-nothing transition to functionality happens remains unclear. Here, in 74 human/hominoid-specific de novo genes, we identified distinctive U1 elements and RNA splice-related sequences accounting for RNA nuclear export, differentiating mRNAs from lncRNAs, and driving the origin of de novo genes from lncRNA loci. The polymorphic sites facilitating the lncRNA–m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 87 publications
2
41
0
Order By: Relevance
“… 3 Many human microproteins have been selected for functional characterization based on high inter-species conservation 2 , 4 and a minimum amino acid (aa) size. However, evolutionarily young microproteins can have biological roles and have for instance been implicated in cell survival, 5 , 6 , 7 human brain development, 8 and cancer. 9 , 10 , 11 Similarly, a lower size cutoff for protein investigations seems unjustified: peptides as small as 11 aa can control morphogenetic development in insects 12 , 13 , 14 and muscle metabolism in humans, 15 respectively, and short bioactive peptides cleaved from bigger precursor proteins can function as peptide hormones.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Many human microproteins have been selected for functional characterization based on high inter-species conservation 2 , 4 and a minimum amino acid (aa) size. However, evolutionarily young microproteins can have biological roles and have for instance been implicated in cell survival, 5 , 6 , 7 human brain development, 8 and cancer. 9 , 10 , 11 Similarly, a lower size cutoff for protein investigations seems unjustified: peptides as small as 11 aa can control morphogenetic development in insects 12 , 13 , 14 and muscle metabolism in humans, 15 respectively, and short bioactive peptides cleaved from bigger precursor proteins can function as peptide hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the recently originated de novo genes in the human lineage show brain-and testis-biased expression profiles (An et al, 2023;D. D. Wu et al, 2011;Xie et al, 2012;Y.…”
Section: Selection Boundaries For De Novo Gene Originmentioning
confidence: 99%
“…Taken together, although there is a consensus for the definition of de novo genes in the field, the list of de novo genes in humans has expanded with the introduction of new genomic technologies. Starting from the initial reports of three human‐specific de novo genes ( CLLU1 , C22orf45 , and DNAH10OS ) by Knowles and McLysaght (2009) and C20orf203 by C. Y. Li et al (2010), dozens of human‐ or hominoid‐specific de novo genes have since been reported, with new genomic technologies such as transcriptome sequencing and ribosome profiling providing evidence of the expression of these new genes (An et al, 2023; J. Y. Chen et al, 2015; Knowles & McLysaght, 2009; C. Y. Li et al, 2010; Ruiz‐Orera et al, 2015; Y. Shao et al, 2019; Vakirlis et al, 2021; D. D. Wu et al, 2011; Xie et al, 2012). According to a recent review by Luuk et al, 82 de novo genes originated recently in the human lineage during the primate evolution (Broeils et al, 2023).…”
Section: The Definition Of De Novo Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of the range of possible mechanisms of de novo gene birth comes from several well-known case studies. The proposed mechanisms are typically expressed as a series of sub-steps involving gains and losses of stable transcription, open reading frames [3], and sequences for nuclear export of RNA [14]. Case studies have also uncovered how certain genomic regions, such as introns [15], and certain tissues like the brains and testes of animals [3] favor the emergence of de novo genes.…”
Section: Introductionmentioning
confidence: 99%